2020
DOI: 10.1101/2020.08.26.20182337
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Role of Social Media in Disseminating Plastic Surgery Research: The Relationship between Citations, Altmetrics and Article Characteristics

Abstract: Background: Social media (SoMe) enables publishers and authors to disseminate content immediately and directly to interested end-users, on a global scale. Alternative metrics (altmetrics) are non-traditional bibliometrics which describe the exposure and impact of an article on freely available platforms such as Twitter, Facebook, Wikipedia and the news. Altmetrics are strongly associated with ultimate citation counts in various medical disciplines, except plastic surgery which represents the rational for this … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Recently, plastic surgery education has jumped on the bandwagon of SoMe services establishing and fostering online presence of residency programs, disseminating plastic surgery research, and empowering patient education 37–40. In general, we found FP to trend across all SoMe platforms with each social networking service displaying distinctive characteristics, such as the social traffic generated during FPAW 2021 and the use of medical terms.…”
Section: Discussionmentioning
confidence: 82%
“…Recently, plastic surgery education has jumped on the bandwagon of SoMe services establishing and fostering online presence of residency programs, disseminating plastic surgery research, and empowering patient education 37–40. In general, we found FP to trend across all SoMe platforms with each social networking service displaying distinctive characteristics, such as the social traffic generated during FPAW 2021 and the use of medical terms.…”
Section: Discussionmentioning
confidence: 82%
“…Previous research has identified weak significant positive associations between metrics of social media dissemination and measures of impact in the plastic surgery literature. 1–7 Although useful for establishing initial trends, these studies have been limited to establishing retrospective correlations between metrics of social media dissemination and bibliometrics. No study to date has attempted to isolate the direct effect of promotional activity on research article dissemination, influence, and impact.…”
mentioning
confidence: 99%